Aerobic Exercise Improves Pulmonary Fibrosis by Improving Insulin Resistance and Inflammation in Obese Mice - Wang, Xishuai; Yi, Xuejie; Tang, Donghui (Frontiers in Physiology, 2022)
Background: Previous studies have demonstrated that obesity is associated with pulmonary fibrosis. We attempted to identify whether regular aerobic exercise (AE) can protect against high-fat diet (HFD)-associated pulmonary fibrosis. Methods: Forty-eight C57BL/6 mice were randomly assigned to four groups: chow group (Ch), chow plus exercise group (CE), obesity group (Ob), and obesity plus exercise group (OE). The mice were fed either an HFD or a chow diet for 16 weeks, and low-intensity aerobic exercise (AE) was performed in the last 8 weeks. We measured the degree of pulmonary fibrosis; pulmonary inflammation; oxidative stress parameters; insulin resistance-related indicators; the number of inflammatory cells in bronchoalveolar lavage fluid (BALF); the mRNA expression levels of IL-10, IL-1β, TGF-β, TNF-α, CXCL-1, IL-17, MMP-9, MPO, NE, and sirt-1; and the BALF levels of CXCL-1, IL-17, TGF-β, IL-10, IL-1β, and TNF-α in lung tissue. Results: AE in obese mice protected against obesity-associated pulmonary fibrosis, chronic inflammation, pro-oxidative/antioxidative imbalance, and insulin resistance. AE ameliorated the HFD-induced inflammatory response and neutrophil infiltration in the lung. AE downregulated BALF levels of CXCL-1, IL-1β, TNF-α IL-17, and TGF-β but upregulated BALF levels of IL-10. AE decreased IL-1β, TGF-β, TNF-α, CXCL-1, IL-17, MMP-9, MPO, and NE mRNA expression levels but upregulated IL-10 and sirt-1 mRNA expression levels in the lung. Conclusions: AE protects against HFD-induced pulmonary fibrosis by improving obesity-associated insulin resistance, chronic low-grade inflammation, and pro-oxidative/antioxidative imbalance. AE improved HFD-induced pulmonary fibrosis by suppressing IL-17, TGF-β, NE, and MMP-9 expression and activating IL-10 and sirt-1 expression.